Melting Properties and Viscosity of SiO2‐CaO‐Al2O3‐B2O3 System. Issue 6 (5th January 2015) - Wang, Lin; Cui, Yaru; Yang, Jian; Zhang, Chen; Cai, Dexiang; Zhang, Jianqiang; Sasaki, Yasushi; Ostrovski, Oleg; Yu, Aibing
<x xml:space="preserve">Abstract</x> This paper investigated melting properties and viscosity of SiO2‐CaO‐Al2O3‐B2O3 fluxes with a mass ratio of CaO/SiO2 from 0.83 to 1.5 and B2O3 content from 5 to 9 wt%. Melting properties of these fluxes were studied using the hot stage microscopy method; viscosity was measured using the rotating cylinder method. Break temperature was also determined from the viscosity change with temperature in flux cooling process. Equilibrium liquidus temperature was calculated using FactSage. Increase in CaO/SiO2 ratio was found to decrease hemispherical temperature and viscosity. The addition of B2O3 did not significantly affect hemispherical temperature but decreased the flux viscosity. Viscosity was analyzed in relation to the flux structure. The increase of the CaO/SiO2 ratio reduced the degree of flux polymerization, and B2O3 apparently acted as a weak network modifier under the low concentration of B2O3. The experimental viscosity was in a good agreement with calculated viscosity using the modified NPL model.